Leveraging Artificial Intelligence to Address Cross-Cultural Workplace Bullying Among International Students in Australia - Du, Jiaxing (International Journal of Global Economics and Management, 2024)
Workplace bullying is a pervasive issue with significant psychological, emotional, and professional repercussions for individuals, particularly in culturally diverse environments. This study explores the potential of artificial intelligence (AI) to address cross-cultural workplace bullying experienced by international students in Australia. By leveraging AI technologies such as natural language processing (NLP), sentiment analysis, and machine learning, organizations can enhance the identification, prevention, and intervention of bullying behaviors. The literature review provides a comprehensive overview of workplace bullying, emphasizing the additional complexities introduced by cultural diversity. Case studies and empirical analyses demonstrate the practical application and efficacy of AI-driven strategies, highlighting significant reductions in bullying incidents, improvements in employee well-being, and enhanced cultural awareness. The study underscores the importance of ethical considerations, algorithm transparency, and continuous training in successfully implementing AI systems. The findings offer valuable insights for employers, policymakers, and educators, contributing to the broader discourse on workplace inclusivity and safety.